Union and distinction in the thought of St. Maximus the Confessor - Törönen, Melchisedec (Oxford early Christian studies, 2007)
Introduction -- Logic -- Tools -- Imagery -- Trinity -- The principles -- Monad and Triad -- Knowing the Trinity -- Christ -- Nature, difference, and number -- Activities and wills -- Union -- Universe, church, scripture -- The creation song -- 'Spiritual hierarchy' -- Transparent words -- Spiritual life and human 'architecture' -- The twofold commandment of love -- Confusion and fragmentation -- Distinction and unification